Costs and Benefits of Mandatory Auditing of For‐profit Private and Not‐for‐profit Companies in Australia. Issue 1 (8th April 2013) - Carey, Peter; Knechel, W. Robert; Tanewski, George
<x xml:space="preserve">Abstract</x> This paper addresses the paucity of research surrounding the mandatory auditing of for‐profit private and not‐for‐profit companies in Australia. We document the various mandatory auditing provisions under the Corporations Act and identify over 22 000 companies that lodge audited accounts with the regulator under federal law. In 2011, 6339 large proprietary companies, 186 small proprietary companies, 2797 foreign‐owned companies, 3985 unlisted public companies and 8404 public companies limited by guarantee had an obligation under the Corporations Act to lodge audited accounts. While large proprietary and foreign‐owned companies have an option to apply to the Australian Securities and Investment Commission for audit relief, we estimate that less than 10% are granted audit exemption. We document that since 1995 an additional 1500 large proprietary companies that should have lodged under the size provisions of the Corporations Act have been granted exemption from doing so (i.e., grandfathered), although these firms appear to be subject to an annual audit even though they do not lodge accounts. We estimate the costs and discuss the potential public interest and firm‐level benefits associated with the mandatory auditing of for‐profit private and not‐for‐profit companies in Australia.